PENERAPAN FUZZY LOGIC DALAM PEMBUATAN PETA ELEMENT AT RISK BENCANA LUAPAN BANJIR SANGAI AIR BENGKULU KOTA BENGKULU - Farouki Dinda Rassarandi; Bungaran Roy Satria Tambunan (Politeknik Negeri Batam, 2019)
Flood is a disaster that can cause loss and damage in various fields, especially infrastructure. One effort to prevent and reduce the impact of flood is by making simulations through spatial modeling in the form map of element at risk. In making map of element at risk, data input in the form of a map downloaded from the Open Street Map containing infrastructures and natural features from disaster simulations made using Fuzzy logic. The application of Fuzzy logic is used to interpret vague statements of the percentage of the building area affected in each classification of flood overflow areas into a logical understanding of the damage classification of